Burden of Rheumatic Diseases in A Rural Community of Bangladesh (Journal of Medicine, 2014)
Objective: To estimate the magnitude, burden of illness and help-seeking behavior of patients with musculoskeletal complaints and to provide incidence of osteoarthritis, low back pain, fibromyalgia, rheumatoid arthritis, gout, and other inflammatory and non-inflammatory rheumatic diseases in a rural community of Bangladesh. Methods: The study was conducted in a few villages near Dhaka city which were considered to be a fairly representative sample of Bangladeshi rural population. Data were collected with the help of modified Community Oriented Program for Control of Rheumatic Diseases (COPCORD) questionnaire and a diagnosis using American College of Rheumatology (ACR) criteria was established. Results: During the 18 months study period, 2685 adults (15 years and above) were included. A total of 441 (M=163, F=278) developed new musculoskeletal (MSK) pain. The incidence rates were 10.9/100 person-years (PY) for the whole population, 8.2/100 PY for males and 13.6/100 PY for females. Nonspecific low back pain (NSLBP), fibromyalgia and osteoarthritis of knee were common MSK problems. A total of 302 patients had complaints of low back pain, of them 204 persons had noninflammatory low back pain; 262 respondents had complaints of knee pain, 38 had satisfied the criteria of knee OA; a total of 116 respondents suffered from fibromyalgia during the study period. Of the respondents (M=17, F=24) 41 had inflammatory arthropathy. Among the incidences of inflammatory arthritis, rheumatoid arthritis 120 (M=101, F=147), spondyloarthropathies 150 (M=252, F=49), ankylosing spondylitis 75 (M=151, F=0), reactive arthritis 50 (M=101, F=0), and psoriatic arthritis 256 (M=0, F=49) per 100,000 / PY respectively were observed, Conclusions: Rheumatic diseases are common in the rural community of Bangladesh, affecting nearly a quarter of adult population. Non-specific low back pain (NSLBP), fibromyalgia and osteoarthritis of knee joints are common joint disorders; point prevalence estimates of most common diagnoses were similar to other community surveys using COPCORD methodology.DOI: http://dx.doi.org/10.3329/jom.v15i2.20685 J MEDICINE 2014; 15 : 125-130